2011
DOI: 10.1007/s11269-010-9761-2
|View full text |Cite
|
Sign up to set email alerts
|

Value of Irrigation Water in Guadalquivir Basin (Spain) by Residual Value Method

Abstract: This paper presents an application of residual value techniques to the economic analysis of irrigation water at the basin level for the Guadalquivir River (Southern Spain). The methodology is simple; the results are robust and consistent with alternative method findings. The average residual value in the basin is 0.31 e/m 3 and according to the to Residual Value Method, the distribution of total Gross Value Added (GVA) of irrigated land is distributed between the different factors of production as follows: (i)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 95 publications
(45 citation statements)
references
References 22 publications
1
38
0
6
Order By: Relevance
“…Exposito and Berbel [50] continue this analysis finding that irrigation water productivity in the basin has stagnated between 2005 and 2012. Berbel et al [51] also studied water productivity ratios, producing a similar figure for 2005. Borrego-Marín et al [31] study the productivity of water based on SEEA-Water methodology.…”
Section: Discussionmentioning
confidence: 87%
“…Exposito and Berbel [50] continue this analysis finding that irrigation water productivity in the basin has stagnated between 2005 and 2012. Berbel et al [51] also studied water productivity ratios, producing a similar figure for 2005. Borrego-Marín et al [31] study the productivity of water based on SEEA-Water methodology.…”
Section: Discussionmentioning
confidence: 87%
“…Our research found that observed irrigation (2010-2013) in our high-intensity sample is 1103 m 3 /ha, that is, less than the allocated water rights but close to subjective economic optima considering water as a limited resource (with a theoretical solution of 1163 m 3 /ha). The regional or basin-level impact of deficit irrigation has been addressed by Berbel, Mesa-Jurado and Piston [20]. They found that for the Guadalquivir Basin, with over 800,000 irrigated ha, the global average RIS for all crops is estimated at 71%, with some crops such as citrus, fruits and rice receiving full irrigation while others such as wheat, cotton or olive groves are cultivated under deficit irrigation regimes.…”
Section: Discussionmentioning
confidence: 99%
“…The residual value method is also a technique applied to valuate water used as an intermediate input to production, when assigning appropriate prices to all inputs but one. Thus, the not accounted value of product is attributed to the residual input, i.e., water [see Young (2005), for a review of the use of this technique, and Berbel et al (2011), for an application in Spain].…”
Section: Methodology: the Economic Value Of Irrigation Watermentioning
confidence: 99%